2017
DOI: 10.1101/151696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individualized connectome-targeted transcranial magnetic stimulation for neuropsychiatric sequelae of repetitive traumatic brain injury in a retired NFL player

Abstract: The recent advent of individualized resting-state network mapping (RSNM) has revealed substantial inter-individual variability in anatomical localization of brain networks identified using resting-state functional MRI (rsfMRI). Such variability may be particularly important after repetitive traumatic brain injury (TBI), which is associated with treatment-resistant depression. RSNM enables personalized targeting of repetitive transcranial magnetic stimulation (rTMS), a focal brain stimulation technique that rel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Additionally, the battery demonstrated sensitivity to improvement with treatment (transcranial magnet stimulation) in a recent case study of traumatic brain injury. 34 Nonetheless, given its novelty, continued work to support the sensitivity of the NIHTB-EB to mental health disease is needed. In addition, calculations for the current NIHTB-EB summary scores and norms have been programmed into a recent update of the NIHTB iPad app for use in ongoing and new studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the battery demonstrated sensitivity to improvement with treatment (transcranial magnet stimulation) in a recent case study of traumatic brain injury. 34 Nonetheless, given its novelty, continued work to support the sensitivity of the NIHTB-EB to mental health disease is needed. In addition, calculations for the current NIHTB-EB summary scores and norms have been programmed into a recent update of the NIHTB iPad app for use in ongoing and new studies.…”
Section: Discussionmentioning
confidence: 99%
“…Research efforts over the past 2 decades have aimed to improve the efficacy and consistency of treatment effects across individuals. While optimal stimulation parameters and dosing are important, one major source of interindividual heterogeneity in treatment outcomes arises from variation in the stimulated site across the spatial extent of the DLPFC (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Therapeutic Brain Stimulation For Depressionmentioning
confidence: 99%
“…Many have suggested that rTMS might be improved by personalizing the stimulation site based on individual differences in connectivity (5,6,9,11,12,16,(92)(93)(94)(95)(96). Recent work demonstrates that SGC FC shows considerable interindividual variation across the spatial extent of the DLPFC (5,92,96).…”
Section: Targeting Tms Based On Individualized Connectivitymentioning
confidence: 99%
“…For example, many reports describe an increase in depressive-like behavior in models of TBI, in good accordance with the clinical studies. The most convincing hallmark of those reports is the concurrence of the depressive-like phenotype, which is recognized despite the fact that these studies are being handled in different institutes using a wide range of parameters, such as age, animal species, injury models, severity of injury and time post-injury 100,101,[114][115][116][117][118][119] . Therefore, these findings suggest that depression is a robust consequence of TBI.…”
Section: Relevance Of Pre-clinical Models Of Tbi To Human Ctementioning
confidence: 99%